ملامح المواجهة التشريعية لجريمتي السحر والشعوذة في التشريع الليبي (Albayan Scientific Journal, 2023)
The practices of witchcraft and related acts are one of the most difficult issues at the present time, because of the negative negative effects that these acts have on the foundations of the Libyan family The Libyan Criminal Code does not explicitly mention witchcraft as a separate crime, and considers these acts to be deception.This research deals with critical analysis the features of the legislative confrontation of the crimes of witchcraft and sorcery in the Libyan legislation. The two crimes of witchcraft and sorcery, and we concluded our study with the most important results and recommendations.